1984
DOI: 10.1002/1097-0142(19840501)53:9<1978::aid-cncr2820530929>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Metastases to the female genital tract: Analysis of 325 cases

Abstract: In order to better define the frequency and patterns of metastasis to the female genital tract, all cases of nonhematopoietic metastases to the adnexa, uterus, vagina, and vulva encountered in patients treated at Barnes Hospital between 1950 and 1981 were reviewed. Three hundred twenty‐five metastatic cancers from 269 patients were recovered. One hundred forty‐nine cases were from extragenital primaries; the remaining tumors were intragenital metastases. Ovary and vagina were the most frequent metastatic sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
238
1
7

Year Published

1985
1985
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 451 publications
(260 citation statements)
references
References 28 publications
7
238
1
7
Order By: Relevance
“…Two clinical features of colon-rectum cancer bearing patients should be recalled. First, as reported by different authors, more than 30% of all metastatic ovarian tumours are actually metastases from colon-rectum carcinomas (Harcourt & Dennis, 1968;Mazur et al, 1984) and unsuspected intestinal tumours are often found in women presenting an ovarian mass initially diagnosed as a primary epithelial ovarian neoplasia (Morrow & Enker, 1984;Lash & Hart, 1987). In these clinical cases CT-guided FNA of ovarian tumours offers an accurate and relatively atraumatic alternative to surgical biopsy in many instances (Sevin & Nedji, 1983) avoiding time-delay and cost of surgery and allowing an adequate treatment of the patient immediately.…”
Section: Resultsmentioning
confidence: 85%
“…Two clinical features of colon-rectum cancer bearing patients should be recalled. First, as reported by different authors, more than 30% of all metastatic ovarian tumours are actually metastases from colon-rectum carcinomas (Harcourt & Dennis, 1968;Mazur et al, 1984) and unsuspected intestinal tumours are often found in women presenting an ovarian mass initially diagnosed as a primary epithelial ovarian neoplasia (Morrow & Enker, 1984;Lash & Hart, 1987). In these clinical cases CT-guided FNA of ovarian tumours offers an accurate and relatively atraumatic alternative to surgical biopsy in many instances (Sevin & Nedji, 1983) avoiding time-delay and cost of surgery and allowing an adequate treatment of the patient immediately.…”
Section: Resultsmentioning
confidence: 85%
“…Unlike the ovary, vagina and cervix, the uterus consists of only 2–5% of cases of extragenital metastatic sites, typically from the breast or gastrointestinal malignancies 2. It has been well understood that uterine metastasis with ovarian involvement is a result of retroperitoneal lymphatic spread from pre‐existing ovarian metastasis; however, sole metastasis to the uterus occurs via hematogenous spread 3.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well understood that uterine metastasis with ovarian involvement is a result of retroperitoneal lymphatic spread from pre‐existing ovarian metastasis; however, sole metastasis to the uterus occurs via hematogenous spread 3. When metastasis to the uterus occurs, it commonly involves the myometrium in 64.5% of cases, both the myometrium and endometrium in 32.7% of cases and only the endometrium in 3.8% of cases 2 which translates to presenting symptoms as abdominal pain, abdominal distension, or commonly AUB. While there were two cases 4, 5 (reviewed in Table 1) that noted an elevation in cancer markers associated with MBC to the uterus, these are often unreliable as indicators of metastasis as was observed in our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Mazur et al [1 ] reported that 27% of the metastases to the female genital tract were a potential source of diagnostic confusion, presenting as possible primary lesions. The ovary was clearly the most common site for an unsuspected metastasis.…”
mentioning
confidence: 99%